1998
DOI: 10.1097/00005344-199807000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of CGS 30440, a Combined Angiotensin-Converting Enzyme Inhibitor and Neutral Endopeptidase Inhibitor, in a Model of Chronic Renal Failure

Abstract: The purpose of these studies was to compare the effects of CGS 30440 (CGS), a dual angiotensin-converting enzyme inhibitor (ACEI)/neutral endopeptidase inhibitor (NEPI) to benazepril (BZ), an ACEI, in a model of five-sixths nephrectomy. The doses of BZ and CGS 30440 tested were 6.5 micromol/kg/day and 2.2 micromol/kg/day. Drugs or vehicle (V) were administered subcutaneously for 6 weeks with dosing initiated 1 week after renal mass reduction. At 6 weeks of receiving drug (7 weeks after five-sixths nephrectomy)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…In addition, omapatrilat reversed the decrease in glomerular filtration rates and reduced elevated plasma creatinine levels. These findings extend the results of previous work showing beneficial effects of the vasopeptidase inhibitor CGS 30440 in alleviating renal injury [16]. They suggest that vasopeptidase inhibition may be a therapeutic approach for retarding progression of renal injury, a condition in which reductions in both blood pressure and proteinuria are considered important targets.…”
Section: Vasopeptidase Inhibitors and Renal Diseasesupporting
confidence: 87%
“…In addition, omapatrilat reversed the decrease in glomerular filtration rates and reduced elevated plasma creatinine levels. These findings extend the results of previous work showing beneficial effects of the vasopeptidase inhibitor CGS 30440 in alleviating renal injury [16]. They suggest that vasopeptidase inhibition may be a therapeutic approach for retarding progression of renal injury, a condition in which reductions in both blood pressure and proteinuria are considered important targets.…”
Section: Vasopeptidase Inhibitors and Renal Diseasesupporting
confidence: 87%
“…Such a possibility is suggested by the reduction in renal ACE activity with omapatrilat being associated with a greater increase in the plasma renin activity than seen with perindopril treatment. In some of the previous studies comparing ACE/NEP inhibition to ACE inhibition, there was a significant difference in blood pressure between the two groups and therefore it was not possible to determine blood pressure-independent effects of agents such as omapatrilat [13,17].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research using the first of the VPIs, omapatrilat, has examined the beneficial effects on ameliorating developing clinical and experimental hypertension [14,15,16]. In addition, an increasing number of studies have explored these agents in models of non-diabetic renal disease [13,17,18]. In a study comparing both selective ACE and NEP inhibitors and another less potent dual ACE/NEP inhibitor mixanpril, albuminuria was partially prevented in a 4 week study in diabetic SHR [19].…”
mentioning
confidence: 99%
“…19,41,42 These studies concluded that vasopeptidase inhibitors conferred greater renal protection than did ACE inhibitors. The major quantitative effect of omapatrilat overwhelming that of enalapril affected proteinuria, as reported by Taal et al 21 in a protocol characterized by delayed treatment with both drugs until 4 weeks after the onset of hypertension.…”
Section: Figurementioning
confidence: 99%